Straits Settlements Blue Book (imports/exports) 1912-1913 vol.57-59 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports during the year 1912';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements form and to other Countries in 1911 and 1912';'Blue Book for the year 1912'.